The opinion of the Italian Society of Occupational Medicine and Industrial Hygiene (SIMLII) on silica-exposure and lung cancer risk / Il punto di vista della Società Italiana di Medicina del Lavoro e Igiene Industriale (SIMLII) su esposizione a silice e rischio di tumore polmonare - Piolatto, G.; Pira, E. (La Medicina del Lavoro, 2011)
Background: The Italian Society of Occupational Medicine and Industrial Hygiene (SIMLII) began a thorough overview of the silica-silicosis-lung cancer question starting in 2005. Methods and Results: The body of information obtained from a number of epidemiological studies, meta-analyses and reviews following the decision of the IARC to classify Respirable Crystalline Silica (RCS) as a human carcinogen (Group 1) led to different conclusions, which can be summarized as follows: basically an increased risk of developing lung cancer is demonstrated and generally accepted for silicotics; the association of lung cancer and exposure to silica per se is controversial, with some studies in favour of an association and some leading to contrary conclusions. Due to methodological problems affecting most studies and the difficulty in identifying the mechanism of action, we agree that the silica-lung cancer association is still unclear. The UE approach is more practical than scientific, in that it recommended the use of “good practices” subject to an agreement with the social partners, without any need to classify RCS as a human carcinogen. However, in 2008 the UE asked the Institute of Occupational Medicine (IOM) in Edinburgh to assess, as a primary objective, the impact of introducing a system for setting Occupational Exposure Limits (OELs) based on objective risk criteria. Conclusion: In the present state of the art SIMLII’s conclusions are: a) There is no need to label RCS with phrase H350i (ex R.49); b) It is of utmost importance to enforce compliance with current OELs; c) Future guidelines specific for silicosis risk should include adequate health surveillance; d) For legal medicine purposes, only lung cancer cases with an unquestionable diagnosis of silicosis should be recognised as an occupational disease.